1997
DOI: 10.1111/j.1467-8624.1997.tb01994.x
|View full text |Cite
|
Sign up to set email alerts
|

Friendships, Peer Acceptance, and Group Membership: Realtions to Academic Achievement in Middle School

Abstract: Two samples of sixth-grade students were followed over time to examine relations of number of reciprocated friendships, peer acceptance, and group membership to academic achievement. In both samples, group membership was the most consistent predictor of grades over time. In Study 2, prosocial behavior, antisocial behavior, and emotional distress were examined as processes that might explain these significant links between peer relationships and academic achievement. Results of longitudinal analyses support a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(67 citation statements)
references
References 31 publications
4
56
0
7
Order By: Relevance
“…This finding is in line with previous research that has shown that above-average students are popular (Coie et al 1990;Newcomb et al 1993;Wentzel and Caldwell 1997). Successful students might be attractive to their classmates, and teachers might know this.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in line with previous research that has shown that above-average students are popular (Coie et al 1990;Newcomb et al 1993;Wentzel and Caldwell 1997). Successful students might be attractive to their classmates, and teachers might know this.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, a negative school environment and negative relations greatly reduced student victims' motivation to come to school and learn. On the other hand, in a study looking at sixth-grade students, peer acceptance was found to be positively related to academic achievement [8]. Specifically, students who were accepted (i.e., high in reciprocated friendship and peer acceptance) were found to experience more positive emotions (i.e., less distress), and lower level of distress was related to higher GPA.…”
Section: Social Relations Teacher's Support and Academic Motivationsmentioning
confidence: 99%
“…It is argued, however, that other channels -such as a pupil's acceptance by peers (Wentzel and Caldwell 1997) or interest in the subject (Trautwein et al 2006) -basically also have the side effect of increasing self-assessment. Therefore throughout the analysis this causal mechanism will be assumed to lie behind the impact of teachers' ratings.…”
Section: Possible Mechanisms For Why Grades Might Influence School Pementioning
confidence: 99%